Analysis of dielectric, impedance and electrical properties of electronic material: Bi(Ni2/3v1/3)O3. (2nd July 2020) - Halder, Sarbasri; Arya, B. B.; Bhuyan, S.; Choudhary, R. N. P.
ABSTRACT: A non-lead electronic sample with chemical composition Bi(Ni2/3 V1/3 )O3 (BNV) has been fabricated via a conventional ceramic technology. The resistive, capacitive and conducting properties of the specimen are examined experimentally. The formation of the sample with orthorhombic crystal system is ensured through X-Ray diffraction spectrum. Detailed analysis of the temperature-frequency dependent dielectric properties affirms the fabricated specimen as a dielectric. The conductivity study gives information about the nature and conduction mechanism of the fabricated dielectric. The impedance spectroscopic technique reveals the role of grain and grain boundaries on the capacitive and resistive properties of the sample. The current density based electric field characteristics show that the sample has low leakage current density (1.2 × 10 −9 A/cm 2 ). This dielectric component entails high dielectric permittivity (98 × 10 2 ), lower loss (8) and excellent excitation response to an electric field, thus it props up to be a potential component in different high-temperature industrial applications.